Media space and the sphere of political communication: a political science analysis - M. M. Abazalieva; M. G. Pavlova (Современная наука и инновации, 2024)
Mass political communication began to act as a multifaceted phenomenon of interaction between political actors through the exchange of information in the process of power struggle or its implementation, including the tactics of indoctrination, and is derived from the media space, because it depends on what services the latter will provide: whether it will be improved digital electronic novelties or outdated technically and morally devices of the last century. Therefore, if in the 1960s or 1970s it was possible to distinguish three areas of the media space (print, radio and television space), now we are talking about the Internet space, which has occupied its leading niche, and with coverage of most of the media space: The Internet space continues to expand, having practically "mastered" print media and television and radio.